PERSEPSI MAHASISWA TERHADAP PERKULIAHAN DARING DI MASA PANDEMI COVID-19 - Sembiring, Desy A. K.; Tijow, Meylani A. (Program Studi Manajemen Pendidikan FKIP Universitas Cenderawasih, 2021)
The world of education is one of the sectors most affected by the Covid-19 pandemic. The pandemic situation forces all educational activities to be carried out by online. This study aimed to look at the development and how students perceived online learning during the Covid-19 pandemic in higher education. The method used in this descriptive study was survey research, where the number of respondents who filled out the questionnaire were 27 students. The results of the study indicated that although students feel they are able to attend lectures, some students think that online learning did not see them as effective. The obstacles encountered by students included limited internet quota facilities, internet instability and learning methods that were considered monotonous and did not stimulate students to be active during teaching and learning activities. These obstacles, alternative solutions that could be offered are optimizing limited offline learning and lecturers are expected to be able to apply student-centered learning methods by referring to a predetermined teaching schedule.Keywords: Students’ Perceptions; Covid-19 Pandemic; Online Learning